The View of the Experts on the Currency Depreciation of Cash Waqf Value - Rahmi Amalia (Universitas Muhammadiyah Malang, 2020)
This study aims to analyze the view of the experts on the currency depreciation of cash waqf value. This research was decriptive qualitatif, the method of collecting data done by documentation and an interview. The data analysis used was content analysis. The result of this study found that the experts all agreed that the risk of decreasing currency value will have an impact on the value of cash waqf.